2005
DOI: 10.1001/archpsyc.62.6.649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoking on Spatial Working Memory and Attentional Deficits in Schizophrenia

Abstract: Cigarette smoking may selectively enhance VSWM and attentional deficits in smokers with schizophrenia, which may depend on nAChR stimulation. These findings may have implications for understanding the high rates of smoking in schizophrenia and for developing pharmacotherapies for cognitive deficits and nicotine dependence in schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
270
5
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(289 citation statements)
references
References 70 publications
9
270
5
4
Order By: Relevance
“…The effects of nicotine on neuropsychological measures in persons with schizophrenia, unlike the effects on the P50 auditory evoked potential less are conclusive. In smokers with schizophrenia, with abstinence from nicotine, working memory is decreased [72,73]. If nicotine is then reinitiated by smoking, working memory deficits are normalized [73].…”
Section: α7 In Learning and Memorymentioning
confidence: 99%
“…The effects of nicotine on neuropsychological measures in persons with schizophrenia, unlike the effects on the P50 auditory evoked potential less are conclusive. In smokers with schizophrenia, with abstinence from nicotine, working memory is decreased [72,73]. If nicotine is then reinitiated by smoking, working memory deficits are normalized [73].…”
Section: α7 In Learning and Memorymentioning
confidence: 99%
“…The administration of both short-and long-acting preparations of nicotine to individuals with schizophrenia has been associated with improved neuropsychological performance (Levin et al, 1996b;Depatie et al, 2002;Smith et al, 2002Smith et al, , 2006Harris et al, 2004;Jacobsen et al, 2004;Myers et al, 2004). Acute administration of the selective a7nAChR partial agonist, DMXB-A, improved P50 gating compared with placebo (Olincy et al, 2006) and administration of the nAChR antagonist, mecamylamine, blocked smoking-associated improvements in performance on attentional and visuospatial working memory (VSWM), implying that nAChR activation mediates smoking-related cognitive enhancement (Sacco et al, 2005). If nAChR activation improves cognitive dysfunction in schizophrenia, then smoking abstinence would be expected to result in deterioration in cognitive performance.…”
Section: Introductionmentioning
confidence: 99%
“…We, therefore, performed the following study to investigate the acute effects of nicotine on cognition in nonsmokers with schizophrenia and healthy controls. We selected a measure of attention as our primary outcome as the nAChR system is thought to play an integral role in the regulation of attentional processes (Mansvelder et al, 2006) and several previous studies have reported an improvement in this cognitive domain following nicotine administration in individuals with schizophrenia (Depatie et al, 2002;Harris et al, 2004;Sacco et al, 2005;Smith et al, 2006). Our primary hypothesis was that nicotine would enhance attention in nonsmokers with schizophrenia and controls; and the secondary hypothesis was that nicotine-associated improvements in cognition would be greater in the schizophrenia group compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…Attentional improvement by nicotinic agents may be a key therapeutic effect for these psychiatric disorders [83,84]. It has been demonstrated that smoking withdrawal induced deficits in both attentional performance and spatial working memory in patients with schizophrenia [85]. Interestingly, these deficits are reversed with smoking and the smoking effect can be blocked by the nicotinic antagonist mecamylamine.…”
Section: The Potential Of Nicotinic Treatment For the Cognitive Impaimentioning
confidence: 99%
“…In a complementary fashion, nicotinic blockade caused significant deficits in the N-back task [91].. Nicotine nasal spray has been shown to improve spatial organization and also improve memory in people with schizophrenia [92,93]. Nicotine also improves eye tracking, memory and attentional function in schizophrenia [84,85,88,92]. Nicotine skin patch treatment in healthy volunteers significantly improved the speed of pre-attentive sensory processing as indexed by mismatch negativity to auditory stimuli in an oddball paradigm [94] Specific nicotinic receptors may be more promising for the improving aspects of cognition in people with schizophrenia .…”
Section: The Potential Of Nicotinic Treatment For the Cognitive Impaimentioning
confidence: 99%